Some Characteristics of Cactus Pear (Opuntia ficus-indica (L.) Miller) Harvested in the Andean Altiplane of Region 2 of Chile - Cerezal , P.; Duarte , G. (Journal of the Professional Association for Cactus Development, 2005)
Cactus pears (Opuntia ficus-indica (L.) Miller) of green coloration were harvested from the Community of Caspana, located at an altitude of 3260 meters above sea level, “El Loa” province, belonging to the Andean altiplane of Atacama Desert in Region 2 of Chile. The objective of the paper was to determine some physical and chemical characteristics of cactus pear pulp(height, diameter, weight, and yield), as well as an integral bromatological test to the fractions of peel, skin, pulp, and seeds. Additionally, the possibility of sensorial acceptance if a portion of milled skin is incorporated in the cactus-pear pulp was studied. The main results were: height, diameter, and weight of: 7,0 ±0.8 cm; 4.9 ±0.3 cm; and 97 ±15.9 g, respectively; low yield in pulp (<37%) and vitamin C (?12,7 mg/100 g) and high contents of soluble solids (14,8 °Brix), of total pericarp (peel and skin), 58.7% and seeds of 6.3%, as well as a relatively high mineral concentration in the skin (1,17%). The sensorial evaluation between the pulp (P) and the pulp with the addition of 25% of skin (PCC) indicated a meaningful favourable difference to the latter. This result is of industrial importance by its economic benefit, as it allows increased yields in the elaboration of semiprocessed products and/or cactus pear concentrated (jams, jellies), among others.